Research Progress in Halogen-Free Flame Retardant Rigid Polyurethane Foam - Kui , Chengyu (Transactions on Engineering and Technology Research, 2024)
The article reviews the research advances on halogen-free flame retardant rigid polyurethane foam (HFR-RPUF), mainly covering three categories of flame retardants: additive, reactive and coating. The additive category includes different types such as organic, inorganic, bio-based, microencapsulated, expandable graphite. The reactive category introduces some flame retardants that can react with isocyanate or hydroxyl groups. The coating category presents examples of some organic, inorganic and carbon nanomaterial flame retardants. The article analyzes the effects and factors of various flame retardants, and contrasts their strengths and weaknesses. Lastly, the article summarizes the characteristics and development directions of HFR-RPUF, and offers future perspectives and recommendations. The review aims to provide references for researchers in the field of flame retardant rigid polyurethane foam.